In vitro antimicrobial effect of essential oil of eucalyptus (Eucalyptus globulus labill) and muña (Minthostachys mollis) - Laura-Ticona, Jhon (2024)
The objective of this research work was to evaluate the antimicrobial effect of 2 oil sources against Staphylococcus aureus and Fecal Coliforms. For the oil extraction, the steam drag method was applied where 5000g of sample was used (muña, Eucalyptus leaves), in which the yield presented: muña 50ml = 0.9268%, eucalyptus 52ml = 0.9717%, a Physicochemical characterization whose result was: in muña oil: peroxide index: 0.75 (Meq / Kg), Iodine index: 6.87 (IV), Acidity index: 1.78 (% FFA), Refractive index: 1.486 (n), density: 0.898 (Kg / L). In eucalyptus leaves: peroxide index: 0.68 (Meq / Kg), Iodine index: 8.08 (IV), Acidity index: 1.82 (% FFA), Refractive index: 1.495 (n), density: 0.845 (Kg / L). Inhibition halos were determined in millimeters (mm), with muña oil in dilutions at 25, 50 and 75% against Fecal Coliforms, where it was at 25%: 9.7950mm, 50%: 10.7467mm, 75%: 13.2700 mm, against Staphylococcus aureus, 25%: 9.9600mm, 50%: 10.7408mm, 75%: 13.1533mm; with dilution of Eucalyptus essential oil against Fecal Coliforms at 25%: 12.0983mm, 50%: 13.2900mm, 75%: 14.5875mm; then against Staphylococcus aureus in 25%: 11.7200mm, 50%: 13.5608mm, 75%: 14.3767. It was possible to establish the inhibitory effect in 2 sources of oils against Fecal Coliforms and Staphylococcus aureus, for which it is concluded that the more dilution of the oil, more microbial inhibition, these species have their respective active principles such as monoterpenes, alcohols, ketones and terpenic oxides that prevent microbial growth.